EBV-LMP1 suppresses the DNA damage response through DNA-PK/AMPK signaling to promote radioresistance in nasopharyngeal carcinoma. Issue 1 (28th September 2016) - Lu, Jingchen; Tang, Min; Li, Hongde; Xu, Zhijie; Weng, Xinxian; Li, Jiangjiang; Yu, Xinfang; Zhao, Luqing; Liu, Hongwei; Hu, Yongbin; Tan, Zheqiong; Yang, Lifang; et al.
Highlights: A new mechanism for EBV-encoded LMP1-mediated radioresistance is proposed. The mechanism relies on the suppression of DDR by LMP1 through inhibiting the DNA-PK/AMPK signaling pathway. The AMPKα (Thr172) reduction was associated with reduced radiosensitivity both in vivo and in vitro and a poorer clinical outcome of radiation therapy in NPC patients, which could provide a mechanistic rationale supporting the use of AMPK activators for enhancing NPC radiotherapy. Abstract: We conducted this research to explore the role of latent membrane protein 1 (LMP1) encoded by the Epstein–Barr virus (EBV) in modulating the DNA damage response (DDR) and its regulatory mechanisms in radioresistance. Our results revealed that LMP1 repressed the repair of DNA double strand breaks (DSBs) by inhibiting DNA-dependent protein kinase (DNA-PK) phosphorylation and activity. Moreover, LMP1 reduced the phosphorylation of AMP-activated protein kinase (AMPK) and changed its subcellular location after irradiation, which appeared to occur through a disruption of the physical interaction between AMPK and DNA-PK. The decrease in AMPK activity was associated with LMP1-mediated glycolysis and resistance to apoptosis induced by irradiation. The reactivation of AMPK significantly promoted radiosensitivity both in vivo and in vitro . The AMPKα (Thr172) reduction was associated with a poorer clinical outcome of radiation therapy in NPC patients. Our data revealed a new mechanism of LMP1-mediated radioresistance and provided a mechanistic rationale in support of the use of AMPK activators for facilitating NPC radiotherapy.